Synthesis of evidence for managing hypertensive disorders of pregnancy in low middle-income countries: a scoping review - María Fernanda Escobar; Nicole Benitez-Díaz; Isabella Blanco-Londoño; Catalina Cerón-Garcés; Evelyn E. Peña-Zárate; Lizbeth A. Guevara-Calderón; Laura Libreros-Peña; Juan Sebastián Galindo (BMC, 2024)
Abstract Background and objectives Hypertensive disorders of pregnancy (HDPs) remain one of the leading causes of maternal mortality globally, especially in Low- and middle-income countries (LMICs). To reduce the burden of associated morbidity and mortality, standardized prompt recognition, evaluation, and treatment have been proposed. Health disparities, barriers to access to healthcare, and shortage of resources influence these conditions. We aimed to synthesize the literature evidence for the management of HDPs in LMICs. Methods A scoping review was conducted in five databases (PubMed, Web of Science, Epistemonikos, Clinical Key and, Scielo) using MeSh terms, keywords, and Boolean connectors. We summarized the included studies according to the following categories: study design, objectives, settings, participant characteristics, eligibility criteria, interventions, assessed outcomes, and general findings. Results Six hundred fifty-one articles were retrieved from the literature search in five databases. Following the selection process, 65 articles met the predefined eligibility criteria. After performing a full-text analysis, 27 articles were included. Three themes were identified from the articles reviewed: prevention of HDPs, management of HDPs (antihypertensive and non-hypertensive management) and pregnancy monitoring and follow-up. The topics were approached from the perspective of LMICs. Conclusions LMICs face substantial limitations and obstacles in the comprehensive management of HDPs. While management recommendations in most LMICs align with international guidelines, several factors, including limited access to crucial medications, unavailability of diagnostic tests, deficiencies in high-quality healthcare infrastructure, restrictions on continuing professional development, a shortage of trained personnel, community perceptions of preeclampsia, and outdated local clinical practice guidelines, impede the comprehensive management of patients. The development and implementation of protocols, standardized guides and intervention packages are a priority.